2021
DOI: 10.5847/wjem.j.1920-8642.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Does shifting to professional emergency department staffing affect the decision for chest radiography?

Abstract: BACKGROUND: The study aims to determine whether shifting to professional emergency department (ED) teams leads to a higher rate of radiologic workup. METHODS: We retrospectively analyzed a total of 2,000 patients presenting to the ED of a tertiary teaching hospital in two time periods: group 1 (G1) comprised 1,000 consecutive patients enrolled from December 21, 2012 to January 5, 2013 (all patients were examined by an internal medicine specialist); group 2 (G2) comprised 1,000 consecutive patients enrolled fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This finding can be explained that older adults have lesser immunity and multimorbidity; therefore, they take more time to recover or become stable before being shifted to the next level of care or discharged from the hospital. Besides, it has been previously reported that older patients have conditions that are more acute and require more emergency resources and more biological and x-ray tests than younger patients, thus requiring longer stay in ED [33][34][35]. Another explanation for this finding might be related to problems in communication, with more time being required to obtain a complete history and perform the physical examination among older patients when compared to younger patients [3].…”
Section: Resultsmentioning
confidence: 99%
“…This finding can be explained that older adults have lesser immunity and multimorbidity; therefore, they take more time to recover or become stable before being shifted to the next level of care or discharged from the hospital. Besides, it has been previously reported that older patients have conditions that are more acute and require more emergency resources and more biological and x-ray tests than younger patients, thus requiring longer stay in ED [33][34][35]. Another explanation for this finding might be related to problems in communication, with more time being required to obtain a complete history and perform the physical examination among older patients when compared to younger patients [3].…”
Section: Resultsmentioning
confidence: 99%